The Cognitive Correlates of Obsessive-Compulsive Disorder: The Predictive Role of Looming Maladaptive Style, Executive Function, Thought-Action Fusion and Metacognition - Maryam Koosheshi; Rahim Yousefi; Ladan Vaghef (پژوهش‌های علوم شناختی و رفتاری)
Obsessive-compulsive disorder (OCD) is one of the most common mental disorders, affecting all aspects of human life. In this study, 300 students from Azarbaijan Shahid Madani University participated through cluster sampling. The participants completed the Threat Magnification Maladaptive Style Questionnaire, the Barkley Deficits in Executive Functioning Scale, the Metacognition Assessment Questionnaire (30 items), the Thought-Action Fusion Questionnaire, and the Yale-Brown Obsessive-Compulsive Scale. The analysis revealed a significant positive correlation between positive beliefs about anxiety and components such as uncontrollability, confidence, self-management, self-control, and self-motivation, with statistical significance at the 1% level. Additionally, a positive and significant correlation was found between positive beliefs about anxiety, uncontrollability, the need for control, maladaptive style of physical threat magnification, and self-organization at the 5% level, and the cognitive component at the 1% level, with symptoms of obsessive-compulsive disorder. Regression analysis indicated that positive beliefs about anxiety, uncontrollability, self-management, and self-motivation significantly predicted the obsessive-compulsive disorder component. Moreover, the predictors of positive belief about anxiety, cognition, maladaptive style of social threat magnification, self-organization, and self-control significantly contributed to predicting obsessive-compulsive disorder component. Given importance of metacognitive beliefs and thought control strategies, influenced by metacognitive beliefs, metacognitive therapy may be useful in predicting and addressing obsessive-compulsive symptoms. Introduction Obsessive-compulsive disorder (OCD) is characterized by obsessions, compulsions, or both. Obsessions are intrusive and distressing thoughts that persistently recur, often leading individuals to engage in compulsive actions to alleviate the distress (Jalal et al., 2023). Research shows that individuals with OCD, as well as non-clinical individuals with high OCD-related scores, exhibit significant cognitive biases. Cognitive models of OCD suggest that exaggerated evaluations of intrusive thoughts and a strong commitment to suppress them play a crucial role in distress and the urge to engage in behaviors such as compulsions, neutralizing actions, thought suppression, reassurance-seeking, and avoidance. When a heightened sense of vulnerability is triggered, it acts as a cognitive threat factor, making individuals more sensitive to danger cues and influencing their cognitive processes with a bias toward threat perception. Similar to other anxiety disorders, maladaptive threat magnification may heighten vulnerability to OCD by imposing a cognitive burden that undermines mental control abilities. Cognitive theory posits that cognitive processes are central to OCD (Jennings, 2022). Literature indicates that individuals with high cognitive threat magnification are more susceptible to anxiety in stressful life events compared to those without this predisposition. However, a notable exception is the strong correlation between social and physical components of threat magnification in women compared to men (Gonzales Diez et al., 2014). Thought-action fusion, a cognitive distortion, can be categorized into probability thought-action fusion and moral distortion (Einstein & Menzies, 2004). Studies on probability and general thought-action fusion in clinical populations reveal high reliability in the general measure. Furthermore, strong links between general thought-action fusion and the probability subscales with OCD characteristics—relative to symptoms of depression and worry—have been confirmed (Myers & Wells, 2013). Recent research has implicated neurological dysfunctions in OCD, including deficits in working memory and executive functions, which may play critical roles in the disorder's assessment and treatment (Bukhari, 2013). Individuals with OCD often exhibit impairments in cognitive control, cognitive flexibility, and inhibitory control. Wells proposed a metacognitive theory of obsession that merges schema theory and information processing theory, highlighting beliefs individuals hold about their cognitive processes (McNicol & Wells, 2012). A study found significant differences in metacognitive beliefs, thought control strategies, and anxiety-inducing thoughts among individuals with generalized anxiety disorder, OCD, dysthymia, and non-clinical individuals (Moin Al-Ghorabaiee et al., 2017). The objective of this study was to address the question: What role do cognitive correlates (specifically, predictors of maladaptive threat magnification style, executive functions, thought-action fusion, and metacognition) play in obsessive-compulsive disorder?